Japan and her dealings with offshoring: An empirical analysis with aggregate data - Pablo Agnese (Institute for the Study of Labor (IZA), 2011)
First moves towards a real understanding of offshoring date back to very recent times. In particular for Japan, the studies conducted so far focus alone on the productivity effects of offshoring at the firm level. Here I carry out the analysis of both the employment and productivity effects at the aggregate level of the industry, covering the years 1980-2005. Moreover, I consider all industries within the economy and take account of both services and materials offshoring. My results suggest that we should expect, on average, a positive effect of services and a negative effect of materials offshoring on employment. However, the effects are rather negligible and only amount to a 1.5 to 2 percent net loss of the change in employment. On the other hand, positive effects on the growth rate of productivity are found as a result of both types of offshoring, with larger effects from services. In particular, the average offshoring industry displays 1.4 to 1.98 additional percentage points for services and 0.48 to 0.64 for materials.
urn:nbn:de:101:1-201104113902
Keywords: F16; J23; O47; 330; offshoring; Japan; employment; productivity; Offshoring; Dienstleistung; Materialwirtschaft; Beschäftigungseffekt; Produktivität; Industrie; Schätzung; Japan